Experimental Study on Aerodynamic Stimulation Technology of Gas Surface Pumping Well - Wang, Huafeng (International Journal of Natural Resources and Environmental Studies, 2025)
The existing underground extraction methods have limitations and timeliness. The cost of mine outburst prevention and gas drainage is high, and the rate of gas drainage is low. The combination of gas surface extraction technology and underground gas extraction can effectively improve the effect of underground gas control. Aerodynamic surging technology is an important completion antireflection and outburst elimination technology for surface gas drainage wells. In Weijiadi Coal Mine, the application of aerodynamic oscillation cavitation technology to mine outburst prevention is one of the methods of cave completion. Through rapid gas pressure fluctuation, the reservoir produces stress damage, which leads to wellbore collapse, increases the exposed area of the reservoir, and destroys the coal seam blocked by the mud pollution channel around the wellbore. Through the suppression and discharge of high gas pressure, the blockage in the coal seam gap-coal ash can be poured into the wellbore, resulting in several self-supporting cracks extending in all directions, so as to realize the effective connection between the wellbore and the reservoir. Through the aerodynamic stimulation technology of the coal seam in the test well, the permeability of the plastic failure area is effectively increased, the efficient extraction of gas near the workload is realized, and the safety hazards of coal seam mining are eliminated in advance. It provides theoretical and practical support for the efficient development of coalbed methane and gas ground treatment, and has important engineering practical significance.